Tourism product design for the department of Cundinamarca in Colombia: a supply and demand analysis (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2022)
The main objective of this research was the construction of a tourism product proposal for the Department of Cundinamarca, Colombia, based on the research obtained from tourists, government officials and institutions, and the department's tourism service providers. For this purpose, Delphi methodology was used, as well as the construction of surveys for the different target groups of interest. The statistical results of the studies on tourism supply and demand served as the basis for the construction of a Tourism Product Design for Cundinamarca based on five rural tourism experiences.
Keywords: Tourism; sustainability; tourist product; rural accommodation